The psychology of Suicide: From research understanding to intervention and treatment - Ali, Huma; Tasnim Rehna (Journal of the Pakistan Medical Association, 2022)
Suicide is considered one of the major causes of death across the globe. The rate of suicide has increased in the recent past and has become a serious problem globally, with nearly one million people committing suicide every year which represents a global standardised rate of 11.4 per 100,000 population i.e., 15 for males and 8 for females.1 From 2000 to 2016, the age-adjusted suicide rate has grown by 30%. Individuals generally have history of mental trauma and distress before attempting suicide. Rate of suicidal ideation is more than that of committing suicide. It is evident that the topic of suicide needs to have a global priority. As clinicians and researchers, it is pivotal responsibility of mental health professionals to establish prevention and intervention programmes to reduce the risk of suicides. Key Words: Suicide, Suicidal risk, Psychology, Intervention, Treatment.